A Bisphosphonate With a Low Hydroxyapatite Binding Affinity Prevents Bone Loss in Mice After Ovariectomy and Reverses Rapidly With Treatment Cessation. (3rd March 2021) - Coffman, Abigail A; Basta‐Pljakic, Jelena; Guerra, Rosa M; Ebetino, Frank H; Lundy, Mark W; Majeska, Robert J; Schaffler, Mitchell B
ABSTRACT: Bisphosphonates (BPs) are a mainstay of osteoporosis treatment; however, concerns about bone health based on oversuppression of remodeling remain. Long‐term bone remodeling suppression adversely affects bone material properties with microdamage accumulation and reduced fracture toughness in animals and increases in matrix mineralization and atypical femur fractures in patients. Although a "drug holiday" from BPs to restore remodeling and improve bone quality seems reasonable, clinical BPs have long functional half‐lives because of their high hydroxyapatite (HAP) binding affinities. This places a practical limit on the reversibility and effectiveness of a drug holiday. BPs with low HAP affinity and strong osteoclast inhibition potentially offer an alternative approach; their antiresorptive effect should reverse rapidly when dosing is discontinued. This study tested this concept using NE‐58025, a BP with low HAP affinity and moderate osteoclast inhibition potential. Young adult female C57Bl/6 mice were ovariectomized (OVX) and treated with NE‐58025, risedronate, or PBS vehicle for 3 months to test effectiveness in preventing long‐term bone loss. Bone microarchitecture, histomorphometry, and whole‐bone mechanical properties were assessed. To test reversibility, OVX mice were similarly treated for 3 months, treatment was stopped, and bone was assessed up to 3 months post‐treatment. NE‐58025 and RIS inhibited long‐term OVX‐induced bone loss, but NE‐58025 antiresorptive effects were more pronounced. Withdrawing NE‐58025 treatment led to the rapid onset of trabecular resorption with a 200% increase in osteoclast surface and bone loss within 1 month. Cessation of risedronate treatment did not lead to increases in resorption indices or bone loss. These results show that NE‐58025 prevents OVX‐induced bone loss, and its effects reverse quickly following cessation treatment in vivo. Low‐HAP affinity BPs may have use as reversible, antiresorptive agents with a rapid on/off profile, which may be useful for maintaining bone health with long‐term BP treatment. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.